Comparing healthcare utilization among health survey respondents with the total population – are respondents representative?. Issue 1 (December 2016) - Agerholm, Janne; Bruce, Daniel; Burström, Bo
Abstract Background Surveys are often used for analysis of health status and healthcare utilization in different socioeconomic groups. However, differential non-response rates may bias results. The aim of this study was to compare register data on outpatient healthcare utilization among respondents to a health survey to that of the total population and to investigate whether socioeconomic differences in outpatient healthcare utilization differ between survey respondents and the total population. Method Data from the Stockholm Public Health Survey 2010 (n  = 30, 767 aged 18 + years) were linked to register data on outpatient healthcare utilization in order to investigate differentials by socioeconomic groups, country of birth and residential areas among respondents, using logistic regression and negative binomial regression. These results were compared to analyses of register data on outpatient healthcare utilization for the total population (n  = 1.6 million aged 18 + years) of Stockholm County. Results Outpatient healthcare utilization was generally higher among survey respondents than in the total population, especially among men. The proportion of individuals having made at least one visit was significantly higher among survey respondents than in the total population but the differences were smaller regarding the average number of visits. Socioeconomic differences in outpatient healthcare utilization between subgroups were largely similar among survey respondents and in the total population. However, individuals born outside Sweden responding to the survey had significantly higher outpatient healthcare utilisation than individuals born outside Sweden in the total population. Conclusion Compared to the total population, a greater proportion of survey respondents had made at least one outpatient visit to the doctor. However, the mean number of registered visits did not differ significantly between survey respondents and the total population. Hence, depending on the outcome measure used survey-based estimates may result in slightly biased prevalence estimates, however, relative differences among survey respondents were to a large degree comparable to relative differences in the total population. In contrast, survey respondents born outside Sweden differed from persons born outside Sweden in the total population to a degree where they may not be representative and comparisons between this group and other subgroups, using survey data, may be biased.